Studi Kasus Asosiasi Pembelian Produk Teknologi pada Toko Elektronik dengan Metode Apriori - Mushleh, Muhammad; Testiana, Gusmelia (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study aims to analyze the purchase pattern of technology products in an electronic store using a priori method. A priori method is a data analysis technique used to identify associative relationships between various items in a dataset. In this study, data on purchase transactions of technology products from electronic stores becomes a database to be analyzed. The results of this analysis are expected to provide useful insights for electronic stores in developing marketing strategies and managing product stock. By knowing common buying patterns between technology products, e-stores can optimize product placement in stores, compile relevant promotional packages, and increase customer satisfaction. The research will involve several stages, including preprocessing of data to prepare datasets, implementation of a priori methods to identify patterns of association, and analysis of results to provide relevant interpretations. Through discussion and conclusion, this study will provide an overview of the implications of research results, recommendations for electronic stores, and limitations that may be encountered.